MEDIATORY ELEMENTS IN THE EFFICIENCY OF COOPERATIVE LEARNING: PREVIOUS TRAINING IN SOCIAL SKILLS AND GROUP DYNAMICS - León del Barco, Benito (Anales de Psicología / Annals of Psychology, 2006)
In the 1990s the first researches, which main objective was to solve questions concerning the efficiency of cooperative learning and the related factors, appeared. Inside this group of researches, there is hardly any which examines the importance of some previous training in social skills and group dynamics, even though many are the writers who emphasize the importance of the social skills the members in a group have and the group maturity. With our research we intend to find significant differences related to the training in social skills and group dynamics, in the roles played within the group, verbal behaviour shown, preformance and individual perception of the group maturity.